Navigating the Ethics and Legalities of Surrogacy in India: A Critical Analysis of the Surrogacy (Regulation) Act of 2021 - Aparna Singh; Vidhi Krishnan (QURU’: Journal of Family Law and Culture, 2025)
This paper aims to critically examine the ethical and legal dimensions of compensated surrogacy in India within the context of the enactment of the Surrogacy (Regulation) Act of 2021, which bans commercial surrogacy and allows only altruistic (non-paid) surrogacy. Through a feminist critical approach, this paper explores the tensions between three main perspectives in the surrogacy discourse: abolitionist (calling for a total ban), reformist (advocating for strict regulations), and libertarian (emphasizing individual freedom and market forces). The research method used is a qualitative study based on document analysis and literature review. The author analyzes national legal sources such as the Surrogacy Regulation Act of 2021, and compares India's legal framework with international practices in other countries such as the United States. In addition, the author examines previous studies on the experiences of surrogate mothers, their socio-economic conditions, and the cultural narratives that influence public perceptions of surrogacy. The analysis reveals that a total ban on commercial surrogacy could create new forms of exploitation by disregarding the value of women's reproductive labor and limiting their economic choices. Previous commercial surrogacy practices in India have indeed shown various issues, such as social inequalities between surrogates and intended parents, as well as weak legal protection. However, rather than endorsing a complete ban, this paper advocates for the implementation of a regulated compensated surrogacy model that acknowledges the physical and emotional labor of surrogates while providing adequate legal and ethical protections. In conclusion, the author emphasizes that a balanced regulation, rather than an outright ban, would better address the socio-economic realities of women in India. By offering an approach that combines reproductive autonomy and legal protection, this model creates a realistic middle ground between unlimited commercialization and the altruistic approach that fails to respond to the real needs of surrogate mothers.